Gaps in coverage and access in the European Union. (30th September 2020) - Webb, E; Palm, W; van Ginneken, E; Lessof, S; Siciliani, L; Hernandez-Quevedo, C; Scarpetti, G
Abstract: Background: At the request of the European Commission, the Observatory on Health Systems and Policies and the HSPM network have undertaken a study to explore gaps in universal health coverage in the European Union and increase the level of granularity in terms of areas or groups where accessibility is sub-optimal. Methods: To explore these gaps more systematically a survey was developed based on the so-called cube model that comprises different dimensions determining health coverage, including population coverage, service coverage and cost coverage. In addition, access can also be hampered by other factors, which relate more to the physical availability of care, a person's ability to obtain necessary care or the attitude of the provider. The survey was sent to country contacts from the Health Systems and Policy Monitor network. Results: Within the diversity of country cases found in the survey, the most significant barriers for accessing health care still seem to be associated with social and income status, rather than specific medical conditions. However, groups like mentally ill, homeless, frail elderly, undocumented migrants are more likely to face multiple layers of exclusion and complex barriers to access. Conclusions: Health system interventions can close access gaps for these vulnerable groups and address inequities in access to care. Through detailed coverage design countries can indeed determine the extent to which financial hardship and catastrophic out-of-pocket spending can be prevented. Furthermore, scope exists to improve current data collection practice.